World commodity outlook 19790: food, feedstuffs, and beverages - Economist Intelligence Unit (Great Britain) (London : Economist Intelligence Unit, 1990)
This book contains world commodity outlook that include food, feed-stuffs and beverages. It also provide series of farming produce under auspices of the economist intelligence unit.
asm; 25/01/19
Loans
Keywords: Food industry and trade; Feeds; Food crops; Business forecasting